MarketPsych : how to manage fear and build your investor identity - Peterson, Richard L., 1972- (Wiley finance series., 2010)
"MarketPsych: How to Manage Fear and Build Your Investor Identity is designed to be a practical guide for financial advisors to learn about the most important, and most ignored, aspect of their work - psychology. This book makes the theoretical practical by translating it into concrete tools and techniques designed specifically for financial advisors. The MarketPsych Handbook contains practical worksheets and planning tools that affect all aspects of the financial advisor's practice. In addition, it details the emotional aspects of running an advisory business, which is crucial for all financial counselors"--